Introduction of alfalfa in the southern Ukraine - Grechana, O. V.; Serbin, A. G.; Bugayov, V. D.; Fukleva, L. A.; Sali, O. O.; Гречана, Олена Володимирівна; Фуклева, Лариса Анатоліївна (My University, 2018)
The gathering of raw materials from cultivated medicinal herbs has several advantages over compounding wild-growing thickets. In particular, it is possible to use mechanized processing techniques, increase the crop yields by improving agronomy and plant breeding, increase the quality of raw materials at optimal terms of gathering and ensuring rational drying conditions. Correct crop rotation, application of fertilizers, protection of plants from pests, diseases and weeds, and also special activities can contribute to increasing the production of raw material of medicinal herbs. The great importance has the development of agronomic recommendations for cultivated forest plants and essential oil plants,introduction of industrial technologies of cultivating medicinal crops and carrying out works of seed production into the practice of plant growing. As we conduct the introduction of medicinal plants, a special place is given to the most important features of the chemical composition in view of its possible variability at the new conditions of existence. In our work the results of the research of samples of 20 sorts of alfalfa in the area of the Zaporizhzhya region are represented. Seed material was obtained from the Institute of Forage and Agriculture of Podillya of the NAAS, Vinnytsya. We received 5g of every type of seed that was not subjected to preliminary processing, 20varieties, different countries of origin. And in the future, we plan to research the chemical composition and the content of the derivatives of 4-oxycoumarin of the harvested raw material, because this group of chemical compounds can accumulate and to have the pharmacological action as anticoagulants. The dropping of alfalfa in the experiment were carried out according to the soil readiness for the optimum terms for the culture. The cultivation technology is generally accepted for alfalfa. Observations, accounting and analysis were conducted in accordance with the Methodological Instructions and the Technique of field experiments. It was established that the height of alfalfa was within the range of 48.8 -74.1 cm. The introduction was carried out on the territory of Institute of Oilseeds National Academyof Agrarian Sciencesof Ukraine (Zaporizhzhya). We made observations of the average climatic indexes within the researched period. In researching the introduction of alfalfa varieties, we investigated of the conformity of growth of alfalfa varieties towards the climatic conditions of Southern Ukraine. The most suitable indicators had the variety of Ukrainian origin (No. 20) Sinucha; it height was 53.3 ± 3.0 cm and weight of dried plant was 25.4 ± 4.3 g.
Keywords: Introduction; Alfalfa; limate Conditions; the South of Ukraine